Thermodynamics : concepts and applications - Turns, Stephen R.; Pauley, Laura L. (Cambridge ; New York, NY : Cambridge University Press, 2018)
"Thermodynamics is one of three disciplines known collectively as the thermal-fluid sciences, sometimes just the thermal sciences: thermodynamics, heat transfer, and fluid mechanics. We begin with a dictionary definition of thermodynamics."--
Conversion factors -- Beginnings -- Thermodynamic properties, property relationships, and processes -- Conservation of mass. Spark-ignition engine geometry -- Energy and energy transfer -- First law of thermodynamics -- Second law of thermodynamics and some of its consequences -- Entropy and availability -- Thermal-fluid analysis of steady-flow devices -- Systems for power production, propulsion, and heating and cooling -- Ideal-gas mixtures -- Vapor-gas mixtures -- Reacting systems -- Chemical and phase equilibrium -- Appendices. Timeline -- Thermodynamic properties of H2O -- Thermodynamic and thermo-physical properties of air -- Thermodynamic properties of ideal gases and carbon -- Various thermodynamic data -- Thermo-physical properties of selected gases at 1 atm -- Thermo-physical properties of selected liquids -- Thermo-physical properties of hydrocarbon fuels -- Psychrometric charts; answers to selected problems.
Includes index.
Keywords: Thermodynamics; Fluid mechanics